Association between the African lycaenid, Anthene usamba, and an obligate acacia ant, Crematogaster mimosae. (26th March 2013) - Martins, Dino J.; Collins, Steve C.; Congdon, Colin; Pierce, Naomi E.
<x xml:space="preserve">Abstract</x> The African lycaenid butterfly, Anthene usamba, is an obligate myrmecophile of the acacia ant, Crematogaster mimosae. Female butterflies use the presence of C. mimosae as an oviposition cue. The eggs are laid on the foliage and young branches of the host plant, Acacia drepanolobium. Larvae shelter in the swollen thorns (domatia) of the host tree, where they live in close association with the acacia ants, and each larva occupies a domatium singly. Anthene usamba are tended by ants that feed from the dorsal nectary organ at regular intervals. Larvae also possess tentacle organs flanking the dorsal nectary organ and appear to signal to ants by everting these structures. Larvae were observed to spend most of their time within the domatia. Stable isotope analysis of matched host plant–ant–butterfly samples revealed that Anthene usamba are δ15N enriched relative to the ants with which they associate. These data, based on the increase in δ15N through trophic levels, indicate that the caterpillars of these butterflies are aphytophagous and either exploit the ant brood of C. mimosae within the domatia, or are fed mouth to mouth by adult workers via trophallaxis. This is the first documented case of aphytophagy in African Anthene. Pupation occurs inside the domatium and the imago emerges and departs via the hole chewed by the larva. The adult females remain closely associated with their natal patch of trees, whereas males disperse more widely across the acacia savannah. Females prefer to oviposit on trees with the specific host ant, C. mimosae, an aggressive obligate mutualist, and avoid neighbouring trees with other ant species. Adult butterflies are active during most months of the year, and there are at least two to three generations each year. Observations made over a 5‐year period indicate that a number of different lycaenid species utilize ant‐acacias in East Africa, and these observations are summarized, together with comparisons from the literature. © 2013 The Linnean Society of London, <mixed-citation id="bij12037-cit-0052" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"><source content-type="journalTitle">Biological Journal of the Linnean Society</source>, <year>2013</year>, <volume>109</volume>, <fpage>302</fpage>–<lpage>312</lpage>.</mixed-citation>